Synthesis of new 1,2,4-triazole and 1,3,4-oxadiazole derivatives derived from 2-ethylsulfanyl benzohydrazide and evaluation of their biological activities / Nafal Nazar Bahjat - Nafal Nazar , Bahjat (2016)
The new 1-acylthiosemicarbazides derivatives 3.3-3.7 were synthesised by the reaction of active intermediate 2-(ethylsulfanyl)benzohydrazide 3.2 with various aryl isothiocyanates. The cyclisation of thiosemicarbazide derivatives in a basic medium (aqueous NaOH, 4 N) yielded compounds 3.8-3.12, while another method was used to prepare 4-amino-1,2,4-triazole-5-thione 3.13. All of the thiosemicarbazide derivatives showed better antioxidant activity than 1,2,4-triazole derivatives in both assays DPPH and FRAP. Hydrogen Atom Transfer (HAT) mechanism was proposed and the Density Functional Theory (DFT) method was used to rationalise the experimental results. 5-[2-(Ethylsulphanyl)phenyl]-1,3,4-oxadiazole-2(3H)-thione 3.14 was prepared by the reaction of 2-(ethylsulphanyl)benzohydrazide with CS2 in KOH. On alkylation of compound 3.14 gave 2,5-disubstituted-1,3,4-oxadiazole derivatives 3.20-3.24. Compound 3.14 showed excellent antioxidant activity in DPPH assay while its alkylated derivatives did not display any antioxidant activity either in DPPH or FRAP assays. Six new hydrazones 3.25-3.30 were prepared and only compounds with substituents 3-OEt-4-OH and 3-OMe-4-OH showed precise antioxidant activity in DPPH assay and in FRAP assay as well. New 2-aryl-5-hydrazino-l,3,4-oxadiazole 3.31 was also synthesized from the reaction of ethyl acetate derivative 3.24 with hydrazine hydrate in dioxane. The reaction of compound 3.31 with some substituted aromatic aldehydes in the presence of ethanol gave new 2,5-disubstituted-1,3,4-oxadiazole derivatives 3.32-3.37. Compound 3.31 showed strong antioxidant activity while oxadiazole derivatives 3.32-3.37 showed some variability in their antioxidant activities. Eight selected 1,3,4-oxadiazoles derivatives were tested against various cancer cell lines. Results revealed some intriguing unexpected levels of activity and the phenolic OH was found to be responsible for the cytotoxicity of oxadiazole derivatives 3.32 and 3.34-3.37. Hydrazone 3.25 substituted with 3-OMe-4-OH was further tested for its antiulcerogenic activity and the result from antiulcerogenic activity was reliable to its DPPH and FRAPs activity, compound 3.25 revealed a significant effect in reducing gastric lesions.